The effect of sheet piles’ inclination angle, number, and distance on seepage through an earthfill dam - Mohammadreza Haghdoost; Seyed Mohsen Sajjadi; Javad Ahadiyan; Reza Norouzi; John Abraham (Ain Shams Engineering Journal, 2024)
The current research deals with the effects of the inclination angle (15, 30, 45, 60, 75, 90, 105, 120, 135, and 150°) of a sheet pile, the number of sheet piles (1–6), and the distance between two vertical sheet piles (2–10 m). The SEEP/W finite element method (FEM) was used to calculate the seepage rate, seepage velocity, and pore water pressure. The outcomes revealed that the maximum decrease in seepage discharge is 34.8 % for a sheet pile with an inclination angle of 105°. By increasing the spacing between two vertical sheet piles, seepage discharge decreases so that the maximum reduction in the seepage discharge was 45.9 % for two vertical sheet piles with a distance of X=10 m. An increase in sheet pile numbers causes a decrease in seepage flow rate so that the maximum reduction in seepage was 50 % when six sheet piles (N=6) were deployed.